Presentation: 20 Years in the Andean World - Iguiñiz Echeverría, Javier (1989)
Allpanchis Phuturinqa celebrates twenty years of existence as a periodical publication in a context in which the celebration of this type of anniversaries is becoming a kind of ritual in the academic and cultural environment of the country. We publishers have decided, in our own way, to honor that practice. Paradox that life brings to a magazine that has dedicated, especially for a certain period, abundant pages to present the rites, rituals and celebrations in the Andean world.